Endoscopic surgery and photodynamic therapy for behign and malignant neoplasms of colon - А. А. Razzhivina; N. V. Ageykina; О. А. Radvanskaya; А. А. Sokolov (Biomedical Photonics)
The review of literature for current methods of endoscopic treatment for colon epithelial neoplasms is represented. Such types of endoscopic interventions as loop electroresection, submucosal dissection, coagulation and destruction of tumors and combination of several options depending on efficiency of previous therapy is analyzed. Limitations of every method, its special aspects and possible complications are described. Special focus is on specifics of neoplasms for which selected methods may be the most effective. Thus, hot biopsy and destruction using high-energy laser is efficient for small flat neoplasms, endoscopic electroexcision – far small pedunculated lesions, and fragmentation is adequate for exophytic tumors more than 2.0 cm. Long-term results of endoscopic treatment, recurrence rates after different options are represented. The literature for photodynamic therapy consists mostly articles about development (on pre-clenecal stage) of new photosensitizers which are effective for colon cancer, new methods of treatment including combination with hyperthermia in low-dose light irradiation etc. The literature data shows the prospectivity of subsequent developments in this field.